Upaya Meningkatkan Kemampuan Guru dalam Memahami Konsep Media Pembelajaran dan Keterampilan Guru PKn Dalam Menggunakan Media Pembelajaran (In Focus) Melalui Metode Pelatihan In-Service-Training di Gugus IV Kecamatan Sukaraja Kabupaten Bogor - Burhanudin, Encep (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2017)
This research aims to know the capacity of teachers in understanding learning media and concepts of learning and skills teachers PKN in using media learning through in-service training methods-training. The method of research used the qualitative Research with engineering support (Research Action class). The results of this research are as follows: Inservice Training Training Implementation can improve the understanding of teachers about Media Pemebelajaran in cluster IV sub district of Bogor regency Well-known; Application of Training In Service Training can improve the skills of teachers in using media learning in Cluster IV sub district of Bogor regency Well-known. Application of inservice training training together can improve the understanding of teachers PKn about media learning and skills teachers PKn in learning to use media (in focus) in Cluster IV Sub Well-known Bogor regency